Incidence of atrial fibrillation is associated with age and gender in subjects practicing physical exercise: A meta-analysis and meta-regression analysis. (15th October 2016) - Brunetti, Natale Daniele; Santoro, Francesco; Correale, Michele; De Gennaro, Luisa; Conte, Giusy; Di Biase, Matteo
Abstract: The link between physical activity and the risk of atrial fibrillation (AF) remains controversial. We therefore sought to further assess by a meta-analysis whether increased levels of physical activity may increase the risk of AF. In October 2015, a PubMed research was conducted for studies that investigated this topic. We identified 11 relevant studies with a total of 81, 787 participants. The pooled analysis did not show an increased risk of AF in subjects practicing physical activity (odds ratio (OR) = 0.92, 95% C.I. = 0.84–1.01, p  = 0.077, I 2  = 90%). However, given the observed large heterogeneity among studies, a subgroup analysis was performed in order to identify possible variables influencing the risk of AF. Significantly higher risk of AF in subjects with reported physical activity was found in studies enrolling exclusively male participants (OR = 7.49, 95% C.I. = 3.12–19.01, p  < 0.001, I 2  = 0%) and subjects younger than 54 years (OR 5.30, 95% C.I. = 3.43–8.20, p  < 0.001, I 2  = 1.7%), while results were opposite in studies enrolling male and/or female participants OR = 0.89 (95% C.I. = 0.81–0.97, p  = 0.01) and subjects older than 54 years (OR = 0.84, 95% C.I. = 0.76–0.92, p  < 0.001). A reverse correlation was also found at meta-regression analysis between age and OR of AF ( p  = 0.047). In conclusion, in our meta-analysis, there is a non-significant trend toward lower risk of AF in subjects practicing physical activity. The risk seems higher in male subjects. A reverse correlation between age and risk of AF seems to be evident. Highlights: In our meta-analysis there is a non-significant trend toward lower risk of AF in subjects practicing physical activity. The risk seems higher in male subjects. A reverse correlation between age and risk of AF seems to be evident.